Resource saving oriented dynamic target adaptive acquisition system in wireless sensor networks - Ke-jiang XIAO; Rui WANG; Li CUI (Tongxin xuebao)
Aiming at dynamic target detection problems in camera sensor networks,a resource saving oriented dynamic target adaptive acquisition system namely EasiRS is built up.EasiRS reuses storage space to decrease the requirement for the storage resources.To solve the problem of continuous images real-time processing caused by dynamics of the monitoring target,an adaptive real-time detection method for image integration detection is proposed.According to the real-time image integration detection,EasiRS does selective transmission for the acquired information to reduce the communication energy consumption and the amount of data that need to transmit the base station.Both indoor and outdoor environmental experiments are conducted.The results demonstrate that although EasiRS needs extra processing time cost,it can decrease storage consumption and transmission energy consumption while maintaining the sensing performance at acceptable level.